2015
DOI: 10.1007/978-3-319-13725-4_6
|View full text |Cite
|
Sign up to set email alerts
|

IgE Immunotherapy Against Cancer

Abstract: The success of antibody therapy in cancer is consistent with the ability of these molecules to activate immune responses against tumors. Experience in clinical applications, antibody design, and advancement in technology have enabled antibodies to be engineered with enhanced efficacy against cancer cells. This allows re-evaluation of current antibody approaches dominated by antibodies of the IgG class with a new light. Antibodies of the IgE class play a central role in allergic reactions and have many properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 177 publications
(239 reference statements)
0
32
0
Order By: Relevance
“…Several of the Fc modifications are being validated in preclinical development and clinical trials and hence it is expected that more therapeutic antibodies with engineered Fc mutations will be approved soon. Beyond IgG, the class of choice for all the approved therapeutic antibodies used for oncologic applications, other classes of antibodies such as IgA ( 175 ) and IgE ( 176 ) are emerging as new options for cancer therapy. These new options, together with the outstanding progress in the development of antibody engineering methods to modify the V regions should lead to a profound impact in the therapy of cancer in the near future.…”
Section: Concluding Remarks and Future Developmentsmentioning
confidence: 99%
“…Several of the Fc modifications are being validated in preclinical development and clinical trials and hence it is expected that more therapeutic antibodies with engineered Fc mutations will be approved soon. Beyond IgG, the class of choice for all the approved therapeutic antibodies used for oncologic applications, other classes of antibodies such as IgA ( 175 ) and IgE ( 176 ) are emerging as new options for cancer therapy. These new options, together with the outstanding progress in the development of antibody engineering methods to modify the V regions should lead to a profound impact in the therapy of cancer in the near future.…”
Section: Concluding Remarks and Future Developmentsmentioning
confidence: 99%
“…Using recombinant monoclonal antibodies (mAb) of the IgE class for immunotherapy of cancer is an innovative approach that has shown promising results in vitro and in vivo. [1][2][3] MAbs for the treatment of cancer are typically designed as IgGs, but use of such molecules has drawbacks, including: 1) relatively low affinity for cognate Fcγ receptors; 2) short half-life in tissues; and 3) the expression of inhibitory Fcγ receptors (FcγRIIb) on immune cells in the tumor microenvironment (TME), which may limit the effector functions and potency of IgGs to promote immune surveillance against solid tumors. 4,5 In contrast, IgE displays up to 10,000-fold higher affinities for and slow dissociation from cognate Fcε receptors on IgE effector cells often found in the TME, lacks inhibitory FcRs, is retained for longer than IgG in tissues, and can exert immune surveillance in Th2-biased environments such as the TME.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies addressed this issue and concluded that systemic hypersensitivity reactions caused by tumor antigen-directed IgE antibodies may not occur in a therapeutic setting. Additionally, no evidence for systemic hypersensitivity reactions due to IgE antibody therapy was seen in various in vivo models (reviewed in [51]). As a result of these in vitro and in vivo observations, an ongoing phase I clinical trial evaluates the potential of IgE antibodies in cancer immunotherapy (NCT02546921).…”
Section: Igementioning
confidence: 99%